2020
DOI: 10.1007/s00726-020-02823-6
|View full text |Cite
|
Sign up to set email alerts
|

Important roles of dietary taurine, creatine, carnosine, anserine and 4-hydroxyproline in human nutrition and health

Abstract: Taurine (a sulfur-containing β-amino acid), creatine (a metabolite of arginine, glycine and methionine), carnosine (a dipeptide; β-alanyl-l-histidine), and 4-hydroxyproline (an imino acid; also often referred to as an amino acid) were discovered in cattle, and the discovery of anserine (a methylated product of carnosine; β-alanyl-1-methyl-l-histidine) also originated with cattle. These five nutrients are highly abundant in beef, and have important physiological roles in anti-oxidative and antiinflammatory reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
232
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(250 citation statements)
references
References 292 publications
(375 reference statements)
5
232
0
13
Order By: Relevance
“…In another study it was shown that anserine, beta-alanyl-3-methyl-l-histidine, a dipeptide, replenished the free radical scavenging enzymes SOD (superoxide dismutase) and preserved catalase and GSH cofactors, while preserving cell integrity and homeostasis, together with a haematological increase in red blood cell volume-to-concentration and an attenuated white blood cellelevation following muscular challenge in healthy men [24]. Dietary intake of anserine, carnosine dipeptides, and other animal-based amino acids including taurine, creatine, and 4-hydroxyproline promote the immunological defence of humans against infections by bacteria, fungi, parasites, and viruses (including coronavirus) through enhancing the metabolism and functions of monocytes, macrophages, and other cells of the immune system [86,87]. Plant-based peptides from soybean have also been shown to modulate cellular immune systems (increased lymphocytes and granulocytes number, increased CD11b(+) cells and CD56(+) natural killer cells), regulate neurotransmitters (decreased adrenaline and increased dopamine), and boost brain function [88].…”
Section: Peptide and Amino Acidsmentioning
confidence: 99%
“…In another study it was shown that anserine, beta-alanyl-3-methyl-l-histidine, a dipeptide, replenished the free radical scavenging enzymes SOD (superoxide dismutase) and preserved catalase and GSH cofactors, while preserving cell integrity and homeostasis, together with a haematological increase in red blood cell volume-to-concentration and an attenuated white blood cellelevation following muscular challenge in healthy men [24]. Dietary intake of anserine, carnosine dipeptides, and other animal-based amino acids including taurine, creatine, and 4-hydroxyproline promote the immunological defence of humans against infections by bacteria, fungi, parasites, and viruses (including coronavirus) through enhancing the metabolism and functions of monocytes, macrophages, and other cells of the immune system [86,87]. Plant-based peptides from soybean have also been shown to modulate cellular immune systems (increased lymphocytes and granulocytes number, increased CD11b(+) cells and CD56(+) natural killer cells), regulate neurotransmitters (decreased adrenaline and increased dopamine), and boost brain function [88].…”
Section: Peptide and Amino Acidsmentioning
confidence: 99%
“…Creatinine (product of creatine), hydroxyproline (a non-proteinogenic amino acid), anserine (a carnosine metabolite), glucosamine (a saccharide), and cysteamine (an aminothiol) are examples of nutrients only found in beef and appeared as discriminating metabolites within their respective nutrient class (Table 1). These nutrients have important physiological, antiinflammatory, and/or immunomodulatory roles 11,12 and low intakes are associated with cardiovascular, neurocognitive, retinal, hepatic, skeletal muscle, and connective tissue dysfunction 11,12 . For example, creatine and anserine provide neurocognitive protection in older adults 13,14 .…”
Section: Untargeted Metabolomics Of Plant-based Meat and Beefmentioning
confidence: 99%
“…Cysteamine, a potent antioxidant, also has neuroprotective effects and is a precursor of glutathione-one of the most potent intracellular antioxidants 15 . Squalene has strong anti-oxidant, anti-bacterial, and anti-tumor activity 16 , while dietary hydroxyproline and glucosamine stimulate collagen biosynthesis and are important for maintaining the structure and strength of connective tissue and blood vessels 11,17 .…”
Section: Untargeted Metabolomics Of Plant-based Meat and Beefmentioning
confidence: 99%
See 1 more Smart Citation
“…DHP is widely used as a therapeutic agent for diseases such as myocardial ischemia [ 7 ], hypertension [ 8 ], and renal diseases [ 9 ]. Additionally, DHP has been used as an additive in animal diets due to its antioxidant ability to protect oil, vitamin A, beta-carotene from oxidation [ 10 ]. Meanwhile, DHP can alter the levels of hormones in the serum, which is beneficial for the promotion of the growth of animals, enhancing reproductive ability, and increasing milking capacity.…”
Section: Introductionmentioning
confidence: 99%